Expansion of "Himantoglossum robertianum" (Orchidaceae) in Madrid: a case study on environmental variables and geographical distribution - Ramos Gutiérrez, Ignacio; Martínez Labarga, Juan Manuel; Araújo Díaz, José; Fernández de Castro, Alejandro G.; Moreno Saiz, Juan Carlos (Mediterranean Botany, 2018)
The increase of the localities of Himantoglossum robertianum in the Community of Madrid region in the last years is studied. We have visited the new discovered populations and characterized their habitats, finding little agreement with the basophilic preferences attributed to the orchid. A model of potential distribution of the taxon has been elaborated showing the southern river basins of the region as the areas of greatest suitability. The lack of data prevents from concluding that the increase of the registered area corresponds with a climatic or land-use change in Madrid region, but the work developed has allowed to properly characterize the distribution and the state of conservation of the species.